2021
DOI: 10.21744/lingcure.v5ns3.1590
|View full text |Cite
|
Sign up to set email alerts
|

flexible-learning journey

Abstract: Philippine higher education has been driven by the urgency of alternative learning modalities from traditional to flexible teaching and learning. Much research has already been embarked on flexible learning. New to the platform, this study purports to document and describe the learning opportunities and influencing factors on the self-efficacy of students in a flexible learning set-up. Using In-depth individual interviews as its method, the qualitative study was administered to higher education students who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
3
3
0
1
Order By: Relevance
“…Be willing to try something and get better results, because if you do it several times, you always get better. (Student A,22,education) This study is consistent with that of Talosa, Javier, & Dirain (2021), who found that when students know that the teacher is technologically skilled in a variety of online tools, they are more eager to learn since most of the participants belong to Gen Z, from which much of the information is taken and delivered through social media.…”
Section: Coping Csupporting
confidence: 83%
See 1 more Smart Citation
“…Be willing to try something and get better results, because if you do it several times, you always get better. (Student A,22,education) This study is consistent with that of Talosa, Javier, & Dirain (2021), who found that when students know that the teacher is technologically skilled in a variety of online tools, they are more eager to learn since most of the participants belong to Gen Z, from which much of the information is taken and delivered through social media.…”
Section: Coping Csupporting
confidence: 83%
“…I tried to balance my studies with household chores at home. I also planned to create, discover, and improve myself (Parent 6,60,housewife) These results affirm the study of Talosa, Javier, & Dirain (2021); Olapane (2019), pointed out that time management could be customarily and emphatically associated with scholarly achievement and that, alternately, poor timing leads to failure and a decreased achievement level. The concept of individuality affirms that no matter how higher institutions prepare the learning environment to be conducive to all involved, individual preparation affects the overall performance of education delivery.…”
Section: A 2 Personal Preparationsupporting
confidence: 53%
“…However, online learning offers the opposite experience to students, where they able to sit in one place, invest their time devotedly for their classes and have extra time for revision. The findings also revealed that online learning has helped the students to have more revision time which contributes to their improvements in learning mathematics [21]. As supported by a research and findings of this research revealed that learning Discrete Mathematics via online does help to improve students' performance [22] [23].…”
Section: B Discussionsupporting
confidence: 58%
“…Having worked with faculty, Harper-Hill et al ( 2022 ) support the concepts of adult education that faculty should participate in the planning process and work from well-stated goals on technology that will be useful in their job. When asked how they gained more knowledge about technologies, instructional design, andragogy, and pedagogy, distance educators responded that they did it through observing others and by doing (Talosa et al, 2021 ). From years of experience as a distance educator, Luongo ( 2018 ) suggests workshops or mentors should be a part of training initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%